The first Americans Prehistory-1600 - Hakim, Joy. (New York : Oxford University Press, 2003)
Presents the history of the Native Americans from earliest times through the arrival of the first Europeans.
History? Why? -- Away with time -- In the beginning -- Feature-Old mysteries and new discoveries -- How the first Americans became Indians -- Feature-Some thoughts on dinosaurs and the earth -- Put on your earmuffs -- Feature -life the far north -- Cliff dwellers and others -- Show- offs -- Feature-People of the Northwest coast -- Taking a tour -- Plains Indians are not plain at all -- Feature- Buffalo on the Great Plains -- Feature-How did they say "Mom"? -- Mound for mound, those are heavy hills -- Feature-Digging up dirt on the mound builders -- Indians of the eastern forests -- People of the long house -- Let's turn north -- Feature-Vikings at L'anse aux meadows -- Feature-How do you know what you know? -- feature- Navigation instruments -- Power of the press -- Boy named Christopher has a dream -- New land is "discovered" -- Feature-from Columbus' pen -- Next voyage -- Stowaways- Worms and a dog -- Sailing around the world -- What's in a name? -- Feature-First map to include "America" -- About beliefs and ideas -- Feature-Stories of how the world began -- New Spain -- Feature-ways of reading and writing -- Feature-Life among the Maya and Aztec -- Feature- Tenochtitlan -- Ponce de Leon, Pizarro, and Spanish colonies -- Gloom, doom, and a bit of cheer -- North of New Spain -- Looking for Cibola with Coronado -- Conquistadors-California to Florida -- Place called Santa Fe -- Las Casas Cares -- Big picture -- From Spain to England to France -- France in America-pirates and adventurers -- Rain, ambush, and murder -- New France -- Feature-Traveling by canoe and portage -- Elizabeth and friends -- Utopia in America -- Lost-a colony -- Feature- from John White's log -- Armada is a fleet of ships -- Keep reading.
Includes bibliographical references (p. 168-169) and index.
Keywords: Indians of North America -- History -- Juvenile literature; America -- Discovery and exploration -- Juvenile literature